The Performance Form of Dzikir Saman, Banjarsari Lebak Banten - Teguh Hartomi; Restu Lanjari; Hartono Hartono (Catharsis, 2023)
Arts is always considered to be related to culture, which becomes a feature. One of the performing arts that continues to exist and develop in Banten is Dzikir Saman. The Dzikir Saman performance is closely related to religious overtones, and thanksgiving is given with aesthetic wrapping. Therefore this research aims to examine the form of Dzikir Saman performances in Banjar Sari, Lebak Banten. This research used qualitative approach and data collection techniques, with observation, interviews, and documentation. From the results of data collection and data analysis, it can be seen that the Dzikir Saman art is divided into three performance structures, the first being tawasul, asyrokol, and saman, which contain elements of performance, such as performers, costumes, music, make-up, property of place and time. Keywords: Form of performance, arts, Dzikir Saman,